Degenerate and non-degenerate In2O3 thin films by pulsed electron beam deposition. (December 2018) - Nistor, M.; Gherendi, F.; Perrière, J.
Abstract: Pulsed electron beam deposition (PED) was used to grow indium oxide thin films on c-cut sapphire single crystalline substrates between room temperature and 500 °C under oxygen gas. A slight difference in oxygen pressure during the PED growth (from 2 × 10 −2 to 1.3 × 10 −2 mbar) has strong effects on the electrical and optical film properties. The indium oxide thin films grown in these conditions changed from a non-degenerate semiconducting behaviour (at 2 × 10 −2 mbar) to a degenerate semiconductor one (at 1.3 × 10 −2 mbar), with a metal-insulator transition at 149 K. This crossover from strong to weak localization, evidenced in the temperature dependent resistivity curves, may be due to the effects of a structural disorder in such films. The direct optical band gap was estimated from transmission spectra taking into account non-degenerate/degenerate behaviour.